Indebtedness in cultural context: The role of culture in the felt obligation to reciprocate. Issue 1 (10th December 2015) - Hitokoto, Hidefumi
Abstract : Based on findings that East Asians report more intensely felt indebtedness than North Americans in response to situations in which they receive everyday help, the intensity of indebtedness was compared across Japanese and North American students using descriptions of indebtedness situations (Study 1) and scenarios (Study 2) in order to examine the cultural processes and meanings of indebtedness. In Study 1, felt intensity of indebtedness in 120 everyday societal situations revealed significantly stronger indebtedness among Japanese than Americans, and when Japanese rated on collectivistic daily situations. In Study 2, scenarios manipulating one's own benefit and other(donor)s' cost showed significant country‐manipulation interactions. The result suggests that the intensity of felt indebtedness among East Asians might be attributable to their inclination to appraise situations in which they receive help in a more relationally concerned manner than their North American counterparts.